Rekayasa Circle Kerja Islami dan Retensi Gen Z : Analisis Kebijakan Karyawan BMH Sulawesi Selatan - Aditya Aditya; Helda Rostiani; Lince Bulutoding; Muhammad Wahyuddin Abdullah (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The low retention of Gen Z employees in the last five years based on LinkedIn Workforce Report data is quite a concern. This research analyses policies related to the management of Human Resources (SDI) at Baitul Maal Hidayatullah South Sulawesi (BMH SULSEL). The research method uses a qualitative approach with data collection techniques through interviews and documentation studies. The results of this study indicate that the employee policies carried out by BMH SULSEL are very effective in increasing Gen Z retention. Through policy engineering by applying Islamic values, BMH SULSEL succeeded in creating a conducive work circle and increasing employee motivation. Policy analysis shows the importance of engineering in shaping a conducive work situation. The implication of this research is the importance of applying Shari'a values in employee policies to improve retention, especially Gen Z.